(untitled) (Nepal Journal of Epidemiology, 2019)
Background: Breast cancer (BC) is reported to be the most common malignancies affecting women worldwide. There is a sharp increase in the BC incidence rate over the past three decades as previously low risk countries are moving towards high -calorie western diets. Few epidemiologic studies along with animal experiments have ascertained the role of dietary fat in developing BC. This study aimed to determine the correlation between per capita dietary fat consumption and incidence of BC. Methods: Three major data bases were used to conduct this correlational study. The data regarding consumption of fat and breast cancer incidence from 88 countries across five continents were extracted. The correlation coefficients between the incidence of BC and the fat consumption from the year 1990 to 2007 were calculated. Results: A statistically significant (P<0.001) correlation between the average fat consumption and the crude BC incidence rate was observed and was more than 0.6, clearly indicating that there is a moderate to strong correlation with fat consumption and incidence of breast cancer (P<0.001). Conclusions: Our observation indicated that increased total fat consumption increases the risk of developing BC. Consumption of dietary fat increases obesity thereby, increasing the risk of BC development. Dietary fat gets stored in the body since they undergo minimum oxidation as compared to carbohydrates and protein thereby, contributing to obesity a known risk factors for BC. Current study strengthens the evidence to support the hypothesis that non-genetic factors contribute to the occurrence of this disease.